The medium of exchange in acquisitions: Does the private information of both acquirer and target matter? - Chemmanur, Thomas J.; Paeglis, Imants; Simonyan, Karen (Journal of Corporate Finance, 2009)
We present a direct test of the choice of the medium of exchange in acquisitions when both acquirers and targets possess private information about their own intrinsic values. We test three hypotheses: first, whether acquirers are more likely to choose a stock offer as their equity is more overvalued; second, whether acquirers facing a greater extent of information asymmetry in evaluating targets are more (or less) likely to use a stock versus a cash offer; and third, whether a cash offer deters competing bids. Our findings are as follows. First, acquirers choosing a stock offer are overvalued and those choosing a cash offer are correctly valued. Second, the greater the extent of acquirer overvaluation, the greater the likelihood of it using a stock offer; further, the greater the extent of information asymmetry faced by an acquirer in evaluating its target, the greater its likelihood of using a cash offer. Third, the extent of an acquirer's under- or overvaluation significantly affects the abnormal returns to its equity upon the acquisition announcement. Finally, the use of cash by an acquirer deters competing bids. We conclude that private information held by both acquirers and targets together determine the medium of exchange.